2019
DOI: 10.3390/fire2020018
|View full text |Cite
|
Sign up to set email alerts
|

Spatial, Temporal and Electrical Characteristics of Lightning in Reported Lightning-Initiated Wildfire Events

Abstract: Analysis was performed to determine whether a lightning flash could be associated with every reported lightning-initiated wildfire that grew to at least 4 km2. In total, 905 lightning-initiated wildfires within the Continental United States (CONUS) between 2012 and 2015 were analyzed. Fixed and fire radius search methods showed that 81–88% of wildfires had a corresponding lightning flash within a 14 day period prior to the report date. The two methods showed that 52–60% of lightning-initiated wildfires were re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
50
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(68 citation statements)
references
References 35 publications
5
50
2
Order By: Relevance
“…Of these 122 events, 25 were excluded due to the inability to find either a flash or stroke that caused the fire within 2 km of the fire start location and 10 days from the report date. These exclusions may be due to the lightning occurring outside of the 2 km radius used to associate lightning to the wildfire, an incorrect classification of the cause of initiation (human instead of lightning-initiated), or they may be long duration holdover events that are beyond the 10 days used in this study as shown in the previous study by Schultz et al [12]. In reference to NLDN data, the 95th percentile lightning distance is a 5 km median error, with the 75th percentile being~1.6 km [42].…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…Of these 122 events, 25 were excluded due to the inability to find either a flash or stroke that caused the fire within 2 km of the fire start location and 10 days from the report date. These exclusions may be due to the lightning occurring outside of the 2 km radius used to associate lightning to the wildfire, an incorrect classification of the cause of initiation (human instead of lightning-initiated), or they may be long duration holdover events that are beyond the 10 days used in this study as shown in the previous study by Schultz et al [12]. In reference to NLDN data, the 95th percentile lightning distance is a 5 km median error, with the 75th percentile being~1.6 km [42].…”
Section: Resultsmentioning
confidence: 96%
“…A backward search from the reported event time was performed in this area to determine the closest lightning flash within 2 km of the start location, similar to the study by Nauslar [39]. This search of lightning data extended back as far as 10 days because 48% of LIWs have been observed to be holdover events [12] that occur when fuels ignited by lightning smolder for days or even weeks before they intensify into a detectable fire [15,22].…”
Section: Data Interrogation and Statistical Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Forest land clearance was a widespread and significant disturbance during colonization of many of the islands, as discussed above, and continues to occur, albeit on a greatly reduced scale, mostly for development [32][33][34]38,[43][44][45][46]. Fire occurs naturally on islands with active volcanoes, but fire from lightning strikes is rare [91,92]. Apart from lava ignitions, most fire affecting the islands' forests is anthropogenic and has increased since human settlement and subsequent population expansion, particularly in the western Pacific, where it occurs in non-native and novel grasslands and along forest edges, and in dry areas of Hawaii and of southern and western Puerto Rico [91,92].…”
Section: Maintenance Of Ecosystem Health and Vitality: Mp Criterionmentioning
confidence: 99%
“…Fire occurs naturally on islands with active volcanoes, but fire from lightning strikes is rare [91,92]. Apart from lava ignitions, most fire affecting the islands' forests is anthropogenic and has increased since human settlement and subsequent population expansion, particularly in the western Pacific, where it occurs in non-native and novel grasslands and along forest edges, and in dry areas of Hawaii and of southern and western Puerto Rico [91,92]. Storms, including hurricanes (in the Caribbean) and typhoons (west of the international dateline) are a regular phenomenon in the tropics and range in their strength and frequency and in their effects on the islands' forests from one point or period of time to another.…”
Section: Maintenance Of Ecosystem Health and Vitality: Mp Criterionmentioning
confidence: 99%